Age at diagnosis and prostate cancer treatment and prognosis: a population-based cohort study. (17th November 2017) - Pettersson, A; Robinson, D; Garmo, H; Holmberg, L; Stattin, P
Abstract: Background: Old age at prostate cancer diagnosis has been associated with poor prognosis in several studies. We aimed to investigate the association between age at diagnosis and prognosis, and if it is independent of tumor characteristics, primary treatment, year of diagnosis, mode of detection and comorbidity. Patients and methods: We conducted a nation-wide cohort study including 121 392 Swedish men aged 55–95 years in Prostate Cancer data Base Sweden 3.0 diagnosed with prostate cancer in 1998–2012 and followed for prostate cancer death through 2014. Data were available on age, stage, grade, prostate-specific antigen (PSA)-level, mode of detection, comorbidity, educational level and primary treatment. We used Cox regression to calculate hazard ratios (HRs) and 95% confidence intervals (CIs). Results: With increasing age at diagnosis, men had more comorbidity, fewer PSA-detected cancers, more advanced cancers and were less often treated with curative intent. Among men with high-risk or regionally metastatic disease, the proportion of men with unknown M stage was higher among old men versus young men. During a follow-up of 751 000 person-years, 23 649 men died of prostate cancer. In multivariable Cox-regression analyses stratified by treatment, old age at diagnosis was associated with poorer prognosis among men treated with deferred treatment (HRage 85+ versus 60–64: 7.19; 95% CI: 5.61–9.20), androgen deprivation therapy (HRage 85+ versus 60–64: 1.72; 95% CI: 1.61–1.84) or radical prostatectomy (HRage 75+ versus 60–64: 2.20; 95% CI: 1.01–4.77), but not radiotherapy (HRage 75+ versus 60–64: 1.08; 95% CI: 0.76–1.53). Conclusion: Our findings argue against a strong inherent effect of age on risk of prostate cancer death, but indicate that in current clinical practice, old men with prostate cancer receive insufficient diagnostic workup and subsequent curative treatment.